Social and cultural anthropology - Rapport, Nigel, 1956-, author.
1 online resource (xii, 548 pages)
Keywords: "Social and Cultural Anthropology: the Key Concepts is an easy to use A-Z guide to the central concepts that students are likely to encounter in this field. Now fully updated, this third edition includes entries on: - Material Culture - Environment - Human Rights - Hybridity - Alterity - Cosmopolitanism - Ethnography - Applied Anthropology - Gender - Cybernetics With full cross-referencing and revised further reading to point students towards the latest writings in Social and Cultural Anthropology, this is a superb reference resource for anyone studying or teaching in this area"--